(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The X-ray diffraction experiments for the liquid Al–Mn alloys was carried out in a wide concentration range at temperatures approximately 50 K higher than the liquidus temperature. The structure factors (SF) and radial distribution functions (RDF) of atoms were calculated from the X-ray scattering (MoKalpha) intensity curves. The analysis of X-ray data showed that the essential changes of local atomic structure of the liquid Al–Mn alloys was in Al-rich region. It have been established, that the concentration dependence of the nearest-neighbor distance is characterized by negative deviations from a linear. This fact denotes the priority of heteroatomic interaction in liquid binary alloys. The prepeak existence in the range from 9 to 25 nm-1 of diffraction vector values is the peculiarity of the obtained structure factor functions. The prepeaks caused by specific arrangement of atoms at distances of 0,4–0,5 nm in dependence of alloy composition.